2022
DOI: 10.3389/fphar.2022.1010937
|View full text |Cite
|
Sign up to set email alerts
|

Ginsenoside Rg1 interferes with the progression of diabetic osteoporosis by promoting type H angiogenesis modulating vasculogenic and osteogenic coupling

Abstract: Ginsenoside Rg1 (Rg1) has been demonstrated to have antidiabetic and antiosteoporotic activities. The aim of this study was to investigate the protective effect of Rg1 against diabetic osteoporosis and the underlying mechanism. In vitro, we found that Rg1 increased the number of osteoprogenitors and alleviated high glucose (HG) induced apoptosis of osteoprogenitors by MTT assays and flow cytometry. qRT‒PCR and western blot analysis suggested that Rg1 can also promote the secretion of vascular endothelial growt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…The effect of MBE on vessels in the fracture environments is not known from the current literature, but anthocyanins have been reported to suppress CD31 expression in tumor environments and platelets [51,71]. On the contrary, type H vessel formation in rodents as well as the expression of CD31 and Endomucin in endothelial cells have been shown to be supported by different ginseng root extracts and ginsenosides, including P. quinquefolium saponin (PQS, from American ginseng), saponin Ophiogonin D, or ginsenoside Rg1 [47,72,73].…”
Section: Discussionmentioning
confidence: 97%
“…The effect of MBE on vessels in the fracture environments is not known from the current literature, but anthocyanins have been reported to suppress CD31 expression in tumor environments and platelets [51,71]. On the contrary, type H vessel formation in rodents as well as the expression of CD31 and Endomucin in endothelial cells have been shown to be supported by different ginseng root extracts and ginsenosides, including P. quinquefolium saponin (PQS, from American ginseng), saponin Ophiogonin D, or ginsenoside Rg1 [47,72,73].…”
Section: Discussionmentioning
confidence: 97%
“…In addition to identifying the type H vessels, Kusumbe and colleagues found that the number of type H endothelial cells and osteoblasts decreases in experimental mice with aging, indicating that age-related OP may be related to the reduction of type H endothelial cells (17). Other scholars also found that type H endothelial cells decreased in other rodent models of different types of OP, such as postmenopausal OP (23), glucocorticoid-induced OP (24), disuse OP (25), and diabetic OP (26). In human subjects, Wang and colleagues first demonstrated the type H vessel is present in the proximal femur near the greater trochanter and coupled with osteoprogenitors.…”
Section: Type H Vessels and Osteoporosismentioning
confidence: 98%
“…Curcumin prevents bone loss and promotes angiogenesis in diabetic OP mice by suppressing the hyper glucose-activated NF-κB pathway to restore osteogenic and angiogenic coupling of BMSC in hyperglycemia (147). In addition, Ginsenoside Rg1 facilitates the secretion of VEGF, triggers the Noggin/Notch signaling pathway, and enhances the interaction between H-type blood vessels and bone formation, leading to an improvement in bone structure in a mouse model of diabetic OP (148). Besides, Salvianolic acid B and Salidroside were also reported to prevent bone loss by enhancing angiogenesis in Glucocorticoidinduced and OVX-induced OP model, respectively, (149,150).…”
Section: The Anti-op Effects Of Herbs and Chemical Ingredients In Tcm...mentioning
confidence: 99%